Upaya Meningkatkan Hasil Belajar IPA Melalui Metode Pembelajaran Interaktif - Sari, Anggy Permata (Journal of Innovation in Teaching and Instructional Media, 2024)
The low learning outcomes of the science subject matter were caused by teachers. After the teacher felt a decrease in students’ interest in science learning. It can be observed that there is still material that seems difficult for children to understand: one of which is related to "everyday material according to its components (single substances and mixtures)". The purpose of this study is none other than to improve the learning outcomes of class V students of SDN 12 Banyuasin I with learning methods. This study is based on Classroom Action Research which consists of two parts. Qualitative data was obtained through observation instruments of single substances and mixtures of students. The interactive learning model is designed to allow students to ask their own questions and get answers. This interactive learning model can also be understood as learning that emphasizes communication between students and students and teachers in direct interaction with learning resources. After seeing the evaluation results, the teacher felt a decrease in students’ interest in science learning. It can be concluded that the average science learning score of class V students of SDN 12 Banyuasin I after using the interactive method where cycle I was 68.0 and cycle II was 89.3, so that the average from Cycle I to Cycle II can be known.